Analysis of Green Open Space Needs in Pekanbaru City based on The Thermal Comfort Index "THI" - Umara Hasmarani Rizqiyah; Nizar Nasrullah; Bambang Sulistyantara (Eduvest - Journal of Universal Studies, 2023)
In 2017 the Mayor of Pekanbaru issued a Letter of Interest in Participating in the Green City Development Program (P2HK). In the letter, it is said that Pekanbaru is ready to fulfill the mandate of law number 26 of 2007. The purpose of this study is to determine and analyze the need for green open space based on the thermal comfort index. The study of this RTH is located in Pekanbaru City, Riau Province. The research tools used consist of hard work (Hardwere) and software (Softwere) which function to retrieve and process data. The hardwere used are; laptops, stationery, mobile phones, GPS, and digital hygrometers. The softwere used are ArcMap 10.3, R Studio, Mr. Word, Mr. Excel, AutoCad, and Photoshop applications. The conclusion obtained is that the area in Pekanbaru is still a lot of green, but in some districts it has a very minimal RTH and is not balanced with other land cover and the districts that are the priority for the next RTH are in Pekanbaru Kota district, Sukajadi, and also Sail District, while for the districts that are not a priority are the East Rumbai district, Rumbai Barat, and the Tenayan Raya area, but because according to the Pekanbaru City RTRW in 2020-2040 the area will be for industrial areas and also residential areas must be carefully planned, especially for city RTH. The most effective addition of green coverage to achieve comfort with a THI value of 26.2 which is 46% at every 62,500m 2.